2013
DOI: 10.1590/1982-43272356201314
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Testing Effect in Learning

Abstract: Abstract:The retrieval of a given piece of information from memory increases the long-term retention of that information, a phenomenon often called "testing effect". The current study aimed to select and review articles on the testing effect to verify the extent and importance of this phenomenon, bringing the main results of recent research. To accomplish this, a systematic review of articles on this subject published between 2006 and 2012 was conducted, a period in which there was an acute increase in the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
(78 reference statements)
0
16
0
3
Order By: Relevance
“…That is, children are provided with high-intensity input but are never required to respond to that input. Prior research on children and adults with typical language has suggested that testing enhances learning over and above gains made simply through study or input (Eisenkraemer, Jaeger, & Stein, 2013;Roediger & Butler, 2011;Rowland, 2014). For example, Karpicke and Roediger (2008) showed that repeated testing increased final recall by 4 SD compared with repeated study.…”
Section: Development Of Interactive Book Readingmentioning
confidence: 99%
“…That is, children are provided with high-intensity input but are never required to respond to that input. Prior research on children and adults with typical language has suggested that testing enhances learning over and above gains made simply through study or input (Eisenkraemer, Jaeger, & Stein, 2013;Roediger & Butler, 2011;Rowland, 2014). For example, Karpicke and Roediger (2008) showed that repeated testing increased final recall by 4 SD compared with repeated study.…”
Section: Development Of Interactive Book Readingmentioning
confidence: 99%
“…Research in several eyewitness studies has also shown that immediate testing improves retention of the studied information over time (Dunning & Stern, 1992;Mackay & Paterson, 2014;Odinot, Memon, La Rooy, & Millen, 2013;Paterson, Eijkemans, & Kemp, 2014; for a review, see Eisenkraemer, Jaeger, & Stein, 2013). The robustness of these findings challenges the claim that an officer's report will be more accurate two or three days post-OIS.…”
Section: The Waiting Periodmentioning
confidence: 99%
“…Conventionally, the educational process has been designed to assess the quality of learning at a few designated standpoints throughout the semester. A number of courses assess the students twice in a semester in form of summative mid-term and final-term exams, with a few-two to five mostly-formative, relatively smaller, low-stake assessment instruments, administered in between [2]. Administering assessments beyond this number is mostly considered bothersome by teachers, as well as by students [2].…”
Section: Introductionmentioning
confidence: 99%
“…A number of courses assess the students twice in a semester in form of summative mid-term and final-term exams, with a few-two to five mostly-formative, relatively smaller, low-stake assessment instruments, administered in between [2]. Administering assessments beyond this number is mostly considered bothersome by teachers, as well as by students [2]. It is especially burdensome for teachers working with large enrolments and/or offering multiple course in parallel-a case highly likely in educational systems of developing nations [3], as well as a growing issue in industrialized world [4].…”
Section: Introductionmentioning
confidence: 99%